Lipoxins in the Nervous System: Brighter Prospects for Neuroprotection - Zhang, Jiayu; Li, Zhe; Fan, Mingyue; Jin, Wei (Frontiers in Pharmacology, 2022)
Lipoxins (LXs) are generated from arachidonic acid and are involved in the resolution of inflammation and confer protection in a variety of pathological processes. In the nervous system, LXs exert an array of protective effects against neurological diseases, including ischemic or hemorrhagic stroke, neonatal hypoxia-ischemia encephalopathy, brain and spinal cord injury, Alzheimer’s disease, multiple sclerosis, and neuropathic pain. Lipoxin administration is a potential therapeutic strategy in neurological diseases due to its notable efficiency and unique superiority regarding safety. Here, we provide an overview of LXs in terms of their synthesis, signaling pathways and neuroprotective evidence. Overall, we believe that, along with advances in lipoxin-related drug design, LXs will bring brighter prospects for neuroprotection.